Perceived teacher-student relationship and growth mindset as predictors of student engagement in foreign student engagement in foreign language learning: the mediating role of foreign language enjoyment - Li, Haoting (Frontiers in Psychology, 2023)
Introduction This study aimed to investigate the relationships between perceived teacher-student relationship, growth mindset, student engagement, and foreign language enjoyment (FLE) among Chinese English learners. Methods A total of 413 Chinese EFL learners participated in the study and completed self-report measures for perceived teacher-student relationship, growth mindset, student engagement in foreign language learning, and FLE. Confirmatory factor analysis was employed to assess the validity of the scales. Structural equation modeling was used to test the hypothesized model. Results The partial mediation model demonstrated the best fit to the data. The results indicated that perceived teacher-student relationship had a direct impact on student engagement. FLE directly influenced student engagement, while growth mindset indirectly affected student engagement through the mediation of FLE. Discussion The findings suggest that fostering positive teacher-student relationships and promoting a growth mindset can enhance FLE, leading to increased levels of student engagement. These results emphasize the importance of considering both the interpersonal dynamics between teachers and students and the role of mindset in foreign language learning.